2019
DOI: 10.5853/jos.2018.03601
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stroke Recurrence after Transient Ischemic Attack: Implications of Etiology

Abstract: Background and Purpose To analyze long-term stroke recurrence (SR) characteristics after transient ischemic attack (TIA) according to initial etiological classification. Methods A prospective cohort of 706 TIA patients was followed up in a single tertiary stroke center. Endpoint was SR. Etiologic subgroup was determined according to the evidence-based causative classification system. Location of TIA and SR was recorded as right, left, or posterior territory. Disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…An index stroke damages the cerebral blood vessels making them prone to subsequent strokes [29]. Also, risk factors that alter the function and lumen of blood vessels such as atherosclerosis increase the probability of recurrence in the same territory as the index stroke [30]. Due to the complexity of stroke recurrence, multiple studies are underway to understand better the factors surrounding lateralization of stroke recurrence [5].…”
Section: Discussionmentioning
confidence: 99%
“…An index stroke damages the cerebral blood vessels making them prone to subsequent strokes [29]. Also, risk factors that alter the function and lumen of blood vessels such as atherosclerosis increase the probability of recurrence in the same territory as the index stroke [30]. Due to the complexity of stroke recurrence, multiple studies are underway to understand better the factors surrounding lateralization of stroke recurrence [5].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, several studies conducted in a wide range of different settings have focused on the association between transient ischaemic attack (TIA) and the risk of stroke [3][4][5][6][7][8][9][10][11][12][13][14]. Whilst these results have shed some light on the association between TIA and stroke, they also have had several limitations that must be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, no specific TIA etiology was found to independently predict a higher stroke risk within our population. Prior studies found that large artery atherosclerosis (LAA) TIA etiology was independently associated with a higher short-term risk of stroke recurrence, ( 34 , 35 ) while no etiological TIA subtype has been identified as robust predictor of increased stroke risk in the long-term ( 36 ). We may speculate that implementing urgent measures to prevent ischemic recurrences within our cohort, as provided by our fast-track care, may have mitigated the unfavorable effect of LAA etiology on future stroke risk.…”
Section: Discussionmentioning
confidence: 99%